Development of Biology Learning Modules Based on Character Education on Ecosystem Material in Class X - Kana Furkonah Pasaribu; Rahmadina Rahmadina (IKIP Mataram, 2024)
Students often encounter difficulties in comprehending biology material, particularly when it comes to ecosystem topics. Learning modules, which serve as teaching resources, have the potential to incorporate character education values. The objective of this study was to create a biology learning module that is valid, practical, and effective, while also focusing on character education for students. The research methodology employed was the Research and Development approach using the 4D model (Define, Design, Develop, Disseminate). Instruments employed in this study included needs analysis through interviews with teachers and questionnaires distributed to students, as well as validation sheets for media experts, material experts, and character education experts. Practicality sheets and an effectiveness sheet, in the form of a character assessment questionnaire, were also utilized. As a result, the study produced a character education-based biology learning module that was deemed highly valid, with a percentage score of 92% from media experts, 90% from material experts, and 87% from character education experts. The practicality results revealed that the module was highly practical, with a percentage score of 89% based on the biology teacher's response, and 90% based on student responses. Moreover, there was a 21% increase in character values among students, with initial data of 54% rising to 75%, suggesting that the character education-based biology module effectively influenced students' character values. Based on the findings of this study, it can be concluded that the learning outcomes achieved by students using the developed module were valid, practical, and effective in facilitating learning activities focused on ecosystem material.